Validation of Astropecten jarli Madsen, 1950 and implications for A. cingulatus Sladen, 1883 (Paxillosida: Astropectinidae) - Lawrence, John M.; Cobb, Janessa (Zootaxa, 2017)
Astropecten is a major paxillosid genus with a widely occurring presence in tropical and temperate seas. Astropecten jarli from off the west coast of Africa, in the Eastern Atlantic Region, was placed in synonymy with Astropecten cingulatus, a widespread species from the Western Atlantic Region, producing the only amphi-Atlantic Astropecten species. Examination of the holotypes of both species and other specimens of A. cingulatus and A. jarli revealed that A. jarli has a greater major radius:minor radius than A. cingulatus at all sizes, a unique adambulacral spine configuration, and different spination on the inferomarginal plates. ANCOVA indicates A. cingulatus and A. jarli have similar major radius:number of superomarginal plates at small sizes but are distinguishable by the number of superomarginal plates in large individuals. The ratio of the width of the paxillar area:width of the superomarginal plates is greater in A. jarli. Some specimens identified as A. cingulatus from the Eastern Atlantic Region do not fit the description of either A. cingulatus or A. jarli. We conclude that A. jarli is morphologically distinct from A. cingulatus and should be recognized as a valid species. Astropecten cingulatus does not have an amphi-Atlantic distribution and is limited to the Western Atlantic Region.